The practical dilemma and solutions of international ship-aircraft encounter rules on sea: A Chinese perspective - Li, Wei; Khan, Mehran Idris (Frontiers in Marine Science, 2022)
The fragmentation of international ship-aircraft encounter (SAE) rules has led to practical difficulties; as such, it is necessary to establish an integrated set of regulations for international SAEs. Based on the theoretical considerations of international law and the rules of the Code for Unplanned Encounters at Sea (CUES) and other SAEs, dispute resolution mechanisms such as international arbitration, diplomatic channels, the International Court of Justice, and Alternate Dispute Resolution have been carefully selected as implementation pathways. However, the global stakeholders are facing the fragmentation of such rules in different ways. To this end, this study thoroughly analyses the fragmentation of the international SEA rules and unresolved pertinent issues. While highlighting the reasons and potential threats of the fragmentation, the present paper also provides Chinese and global perspectives to resolve the issues with appropriate recommendations collectively. It concludes that such fragmentation of navigation rules and dispute resolution mechanisms—if effectively addressed with harmonising existing rules and unified international rules—can centrally resolve the encounters between ships and aircraft in the process of international voyages and form a basic, unified understanding of some of the most representative issues.